The Superiority of Customary Law over Islamic Law on the Existence of Inheritance: Reflections on Snouck Hurgronje's Reception Theory - Muhammad Jazil Rifqi (Millah: Journal of Religious Studies, 2021)
In colonial history in the Dutch East Indies, customary law was superior to Islamic law. By utilizing the historical approach of social thought, this article aims at exploring how and why customary inheritance law was more applicable than Islamic inheritance law. After observing the practice in several areas, including in Surambi Masjid, Snouck Hurgronje found that customary law dominated people's lives. In turn, this idea was implemented in Dutch legal regulations that weakened the roles of penghulu of the Religious Courts in resolving family and inheritance issues that required approval from the District Court judges. In addition, the penghulu’s decision was not valid if it was not in line with customary law. Based on Hurgronje’s advice, the competence of the Religious Court at inheritance was transferred to the District Court. He considered that inheritance was under the state’s authority, and at the same time, it had not been fully accepted by customary law.